A review on selected heterogeneous photocatalysts for hydrogen production. (10th June 2014) - Acar, Canan; Dincer, Ibrahim; Zamfirescu, Calin
SUMMARY In this study, visible light‐driven heterogeneous photocatalysts for hydrogen production are comparatively assessed based on technical, environmental, and cost criteria. The photocatalysis systems are compared with respect to their (i) rate of hydrogen generation per gram; (ii) rate of hydrogen generation per m2 of the specific surface area; and (iii) the band gap energy. The photocatalysis systems are also compared and discussed in terms of flammability, reactivity, and their impact on living systems' health. Furthermore, the costs of the required components of the photocatalysis systems are ranked. In addition to individual photocatalyst comparison, seven photocatalyst groups are ranked and compared. The results show that TiO2‐C‐362 and Ag0.03Mn0.40Cd0.60S show the highest in terms of µmol/h‐gcat and µmol/h‐m2cat, respectively, and TiO2‐C‐362 has the highest overall rankings. The Zn/In/S‐based photocatalyst groups show the highest hydrogen production rate in terms of µmol/h‐gcat and µmol/h‐m2cat. Overall, Cd/S/Zn has the highest rankings when cost and health and environmental impact criteria are taken into account. Copyright © 2014 John Wiley & Sons, Ltd.